Geotechnical centrifuge modelling of the behaviour of a compressible clay horizon underlying a reinforced sand foundation - Van Rooy, J.L. (Jan Louis) (University of Pretoria, 2014)
Dissertation (MSc)--University of Pretoria, 2014.